PERAWATAN LUKA PASIEN POST ORIF PATELLA SINISTRA MENGGUNAKAN NaCl 0,9% DAN GENTAMICIN SULFAT - Rosa Nur Triana; Sudiarto; Fida Dyah Puspitasari (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2023)
Fracture is any crack or break caused by trauma and physical activity. A direct blow to the kneecap area can result in a patella fracture. Open Reduction Internal Fixation (ORIF) surgery is an option for treating fractures using the surgical method, requiring wound care to speed up healing and prevent infection. Mixing gentamicin sulfate and 0.9% NaCl solution in treating wounds can speed up the wound healing process by helping the formation of new granulation tissue. The purpose of this study was to describe wound care using 0.9% NaCl and gentamicin sulfate in post debridement fracture patients + left patella orif. This research is included in descriptive research and a case study research design is used in scientific writing. Interviews and wound assessment observations were used for data collection. Patients with patellar orif fractures and post-debridement fractures were eligible to participate as long as they met the inclusion criteria. Patients with infected post orif patella fractures and children under 18 years of age were excluded. Based on the results of wound care for 5 meetings, the patient's wound appeared to be improving with slight changes in the red and pink wounds. It can be concluded that wound care in post debridement fracture patients + left patella orif experienced wound healing.